UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATERI MENGHITUNG PAJAK PENGHASILAN DALAM MATA PELAJARAN IPS MELALUI PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER PADA SISWA KELAS VIII SEMESTER GENAP TAHUN PELAJARAN 2011/2012 DI SMP KRISTEN SELAT KABUPATEN KAPUAS - Ratuni Ratuni (Universitas Lambung Mangkurat, 2013)
Teachers creativity is needed to create the learning that is able to increase the motivation and students achivement. One of those is the ability to choose an appropriate learning model. Numbered Heads Together is one of those Motivational learning model that is believed able to increase the motivational and students achievement because it is oriented to students. The research aims to : (1) Increase the students learning motivation. (2) Increase social subject learning achievement of VIII grade of SMP Kristen Kapuas Kecamatan Selat Kabupaten Kapuas. The research subject is students of VIII grade of SMP Kristen Kapuas of 28 srudents, consist of 11 male and 17 female. The variabel of the research consist of student learning activity and students learning achievement. The gathering data is used observation sheet, questionnaire, test, notes, documentation. The research result showed that the score average of teacher’s cycle I was 3.0 (good category), the average of teacer’s skill in cycle II was 3.4 (excellen category). The increasing learning result gained from actuating test each cycle, at cycle I goot 75,00 % and cycles II goot 92,86 %. Student learning activities of grade of SMP Kristen Selat Kapuas at the theme of counting income tax was also increase. It was described of the average of student’s activity in the first cycle from 2,91 to 3,16 increase at second cycle.Key words: Cooperative approach, Numbered Heads Together type, Motivation, learning achievement.